2003
DOI: 10.1016/s0304-3959(02)00331-7
|View full text |Cite
|
Sign up to set email alerts
|

Affective associative learning modifies the sensory perception of nociceptive stimuli without participant's awareness

Abstract: The present experiment examined the possibility to change the sensory and/or the affective perception of thermal stimuli by an emotional associative learning procedure known to operate without participants' awareness (evaluative conditioning). In a mixed design, an aversive conditioning procedure was compared between subjects to an appetitive conditioning procedure. Both groups were also compared within-subject to a control condition (neutral conditioning). The aversive conditioning was induced by associating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 60 publications
3
34
0
1
Order By: Relevance
“…Although this may have affected the inability of pleasant pictures to modulate pain, by making them deviate less from neutral data than unpleasant images (Fig. 1), such inability was also found in previous studies that did not eliminate sexual material (Wunsch et al, 2003). Human conditioning theories state that the transfer of affective reactions from an unconditioned to a conditioned stimulus is facilitated when both belong to the same affective category (Cook et al, 1986;Hamm et al, 1989;Ohman and Mineka, 2001).…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…Although this may have affected the inability of pleasant pictures to modulate pain, by making them deviate less from neutral data than unpleasant images (Fig. 1), such inability was also found in previous studies that did not eliminate sexual material (Wunsch et al, 2003). Human conditioning theories state that the transfer of affective reactions from an unconditioned to a conditioned stimulus is facilitated when both belong to the same affective category (Cook et al, 1986;Hamm et al, 1989;Ohman and Mineka, 2001).…”
Section: Discussionmentioning
confidence: 68%
“…A general effect of aversive pictures on behavioral pain responses was shown in previous studies (de Wied and Verbaten, 2001;Meagher et al, 2001;Wunsch et al, 2003). Although human pain scenes were included in these, their specific effect was never assessed.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…[14][15][16]39,40 The majority of evidence has indicated that negative mood or the expectation of increased pain significantly exacerbate pain, whereas positive mood, good coping skills or the expectation of reduced pain prominently attenuate pain. [41][42][43][44][45][46][47] These factors may explain the increased pain reports inside the scanner. Several studies also examined the effect of MR scanner-associated noise on brain activation patterns.…”
Section: Discussionmentioning
confidence: 99%
“…Awareness data of two participants were missing. However, data of all participants were included in statistical analyses as contingency awareness is not a necessary feature for differential fear conditioning in pain 52 .…”
Section: Contingency Awarenessmentioning
confidence: 99%